Improving Islamich Higher Education: Lessons From John Dewey and Ivan Illich - Muhammad Adib Abdushomad (International Journal of Nusantara Islam, 2014)
Apart from these research are trying to understand, economic and political philosophy, or ideology, underlies approaches that undertaken by government to deliver their services. In relation to the above discussion, this paper aims to elaborate the two thinkers; John Dewey and Ivan Illich to see how Islamic education could meet human needs, particularly to enhance the institutions that enable people to develop their full potentiality. This paper will elaborate the two thinkers’ perspectives and bring it into real situation in my department. The first section will capture the debate on education and schooling, includes the aims of education, and also approach to educational policy. Following this, the second section is going to analyses John Dewey and Ivan Illich perspectives on education. Thirdly, reconstruct a new way of thinking based on ideological approaches for the directorate of Islamic Higher education (DOIHE) to find out a better way to address some problems occurs recently.